Intercropping of orthosiphon stamineus (benth) with hevea brasiliensis (willd) and durio zibethinus (murr) amended with various organic fertilizers and their financial analysis - Affendy Hassan (2009)
Orthosiphon stamineus (Benth) or Misai kucing is a potential herb that can be intercropped under shade trees. The study was carried out at the nursery of School of International Tropical Forestry (SITF) Universiti Malaysia Sabah and fields of smallholders (rubber and durian) at Papar, Sabah. The objectives of this study were to determine the light intensity suitable to the growth of O. stamineus with different organic fertilizer applications, to evaluate the growth of O. stamineus rubber and durian canopies, to determine the soil properties and nutrient uptake of O.stamineus for the various fertilizer application regimes and to determine the financial feasibility of O. stamineus yields intercropped with rubber and durian. Amongst the relative light intensity (RLI) regime, 50% RLI was better than 30% and 100% RLI. The field planting distance used was 1.5 m X 0.45 m. Higher rate of fertilizer application gave higher yields of O. stamineus. Chicken dung was the best fertilizer followed by oil palm EFB and cow dung. The productivity using oil palm EFB and cow dung was smaller compared to chicken dung. Soil physical properties did not show any influence on the growth and yield of O. stamineus. However, the soil chemical properties influenced the growth based on the type of fertilizer applied. Project simulations showed that, intercropping of O. stamineus under rubber (0.9 kg fertilizer per plant) and under durian (0.9 and 0.6 kg per plant) using chicken dung is the most feasible financially. However, the other fertilizers are not feasible due to low yield and high cost of fertilizer per unit kilogram. The NPV under rubber was RM 47,413 (0.9 kg per plant only) and for durian was RM 91,751 (0.9kg per plant) and RM 60,414 (0.6kg per plant). The revenue and cost affect the NPV, IRR, B/C ratio and the payback period.